DETEKSI DINI ATRIAL FIBRILASI UNTUK MENURUNKAN RISIKO STROKE - Suryantarini, Ni Wayan Puspa Wijaya (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Stroke is one of the major causes of death and contributes to loss of productivity in daily activities throughout the world. Every year it is estimated that there are 13,7 million new cases of stroke with a possibility of 1 in 4 people over 25 years will developing stroke. Stroke has various pathogenesis depending on the age at which the onset of stroke and the type of stroke. The increase in prevalence and mortality due to stroke has prompted many studies to examine stroke risk factors as well as early detection and management, including prevention. One common form of cardiac arrhythmia, is atrial fibrillation or AF, is one of the triggering factors for stroke with a five-fold risk. AF often does not manifest the symptoms in patients. Early detection of AF in all individuals, especially those at high risk of AF and stroke, is crucial to initiating early intervention and reducing the possibility of complications. Various devices have been developed to detect the occurrence of AF in asymptomatic and at-risk patients. This literature aims to explain how to detect early atrial fibrillation, including screening for AF symptoms, physical examination, ECG examination, use of technological devices, stratifying the risk of stroke in AF patients, and finally the prevention strategies for both AF and stroke.